2019
DOI: 10.47176/mjiri.33.151
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of major depressive disorder in the general population of Iran: A systematic review and meta-analysis

Abstract: Depression has an important role in people's lives. Many studies have investigated the prevalence of depressive disorders in Iran during past decades. →What this article adds: This systematic review and meta-analysis revealed the considerable prevalence of major depression disorder among Iranians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…To the best of our knowledge, this systematic review and metaanalysis included the largest number of studies and largest overall sample size estimating MDD prevalence in the Chinese population to date. The point prevalence in this meta-analysis was 1.1% (95% CI: 0.9-1.4%), which is significantly lower than the corresponding findings of previous meta-analyses in other countries; for instance, the point prevalence was 4.1% (95% CI: 3.1-5.5%) in a meta-analysis of MDD in Iran (62). Similarly, the overall 12-month prevalence (1.6%; 95% CI: 1.0-2.5%) and lifetime prevalence (1.8%; 95% CI: 1.5-2.2%) estimates of MDD in this meta-analysis were noticeably lower than rates from previous studies; for instance, in the World Mental Health Survey (WMH) the mean 12-month prevalence of MDD was 5.9% and ranged from 3.8% to 10.4% while the mean lifetime prevalence of MDD was 11.1%, and ranged from 6.5% to 18.4% in low-middle income countries (5).…”
Section: Discussioncontrasting
confidence: 87%
“…To the best of our knowledge, this systematic review and metaanalysis included the largest number of studies and largest overall sample size estimating MDD prevalence in the Chinese population to date. The point prevalence in this meta-analysis was 1.1% (95% CI: 0.9-1.4%), which is significantly lower than the corresponding findings of previous meta-analyses in other countries; for instance, the point prevalence was 4.1% (95% CI: 3.1-5.5%) in a meta-analysis of MDD in Iran (62). Similarly, the overall 12-month prevalence (1.6%; 95% CI: 1.0-2.5%) and lifetime prevalence (1.8%; 95% CI: 1.5-2.2%) estimates of MDD in this meta-analysis were noticeably lower than rates from previous studies; for instance, in the World Mental Health Survey (WMH) the mean 12-month prevalence of MDD was 5.9% and ranged from 3.8% to 10.4% while the mean lifetime prevalence of MDD was 11.1%, and ranged from 6.5% to 18.4% in low-middle income countries (5).…”
Section: Discussioncontrasting
confidence: 87%
“…According to a national study conducted in Iran, depression was the third health problem in this country 2 . Furthermore, the studies showed that depression was higher in adult females (about 1.7 times higher), compared to males 7 , 8 . In Iran, major depression is the most prevalent mood disorder (2.98 % in total, 4.38 % in adult females) 9 .…”
Section: Introductionmentioning
confidence: 93%
“…It must also be noted that the study is done on an Iranian sample of depressed patients; therefore, cultural factors of MDD should have been accounted for to be able to make more firm conclusions based on the reported results. It has been noted in a recent epidemiological review that the prevalence of MDD is twice as high for women in Iran and some neighboring countries (Gharraee et al., 2019 ) thus the cultural and geographical context in relation to sex may have affected the result tendencies and thus must be considered in future investigations to understand sex differences in treatment response to rTMS.…”
Section: Discussionmentioning
confidence: 99%